Impact, economic evaluation, and sustainability of integrated vector management in urban settings to prevent vector-borne diseases: a scoping review - Jorge Marcos-Marcos; Antonio Olry de Labry-Lima; Silvia Toro-Cardenas; Marina Lacasaña; Stéphanie Degroote; Valéry Ridde; Clara Bermudez-Tamayo (BMC, 2018)
Abstract Background The control of vector-borne diseases (VBD) is one of the greatest challenges on the global health agenda. Rapid and uncontrolled urbanization has heightened the interest in addressing these challenges through an integrated vector management (IVM) approach. The aim was to identify components related to impacts, economic evaluation, and sustainability that might contribute to this integrated approach to VBD prevention. Main body We conducted a scoping review of available literature (2000-2016) using PubMed, Web of Science, Cochrane, CINAHL, Econlit, LILACS, Global Health Database, Scopus, and Embase, as well as Tropical Diseases Bulletin, WHOLIS, WHO Pesticide Evaluation Scheme, and Google Scholar. MeSH terms and free-text terms were used. A data extraction form was used, including TIDieR and ASTAIRE. MMAT and CHEERS were used to evaluate quality. Of the 42 documents reviewed, 30 were focused on dengue, eight on malaria, and two on leishmaniasis. More than a half of the studies were conducted in the Americas. Half used a quantitative descriptive approach (n = 21), followed by cluster randomized controlled trials (n = 11). Regarding impacts, outcomes were: a) use of measures for vector control; b) vector control; c) health measures; and d) social measures. IVM reduced breeding sites, the entomology index, and parasite rates. Results were heterogeneous, with variable magnitudes, but in all cases were favourable to the intervention. Evidence of IVM impacts on health outcomes was very limited but showed reduced incidence. Social outcomes were improved abilities and capacities, empowerment, and community knowledge. Regarding economic evaluation, only four studies performed an economic analysis, and intervention benefits outweighed costs. Cost-effectiveness was dependent on illness incidence. The results provided key elements to analyze sustainability in terms of three dimensions (social, economic, and environmental), emphasizing the implementation of a community-focused eco-bio-social approach. Conclusions IVM has an impact on reducing vector breeding sites and the entomology index, but evidence of impacts on health outcomes is limited. Social outcomes are improved abilities and capacities, empowerment, and community knowledge. Economic evaluations are scarce, and cost-effectiveness is dependent on illness incidence. Community capacity building is the main component of sustainability, together with collaboration, institutionalization, and routinization of activities. Findings indicate a great heterogeneity in the interventions and highlight the need for characterizing interventions rigorously to facilitate transferability.